Taṭbīq Ṭarīqah bi al-Kalimāt al-Mutaqāta’ah litarqiyyah Qudrah al-Ṭullāb ‘ala Tarkīb al-Ḥurūf al-Hijā’iyyah - Nur Rahmi (DAYAH: Journal of Islamic Education, 2020)
Vocabulary is a set of language words. Vocabulary is important in the process of developing student language. The more vocabulary the students master, the more he talks and writes. Teaching writing begins with writing letters, words and then sentences. Sometimes the mistake in word writing causes wrong meaning. Therefore, Arabic students must learn and understand it. This research was conducted at the Babun Najah boarding school where students learn vocabulary at the school. However, the researcher found mistake from students in vocabulary writing, such as installing letters on the word "مطعم " write "مضعم " dan"مطعام" and so forth. One of the main reasons for teaching problems is that the teacher does not apply interesting methods and media to teach vocabulary, especially in writing with correct hijaiyah letters. Therefore, the researcher wants to apply the Guide Teaching method with crosswords as a solution to this problem. The purpose of this study is to know the condition of students in the process of teaching implementation on the application of Guide Teaching methods with crossword puzzles and the effectiveness of both to improve students' ability to compile hijaiyah letters. This study uses the quasi-experiment method. The researcher took a sample of 19 students from the second grade (d) in one group at the Babun Najah boarding school and collected data in the form of observation and tests. To analyze data, researchers used a test code related to the t-test. The results showed that the application of the Guide Teaching method with crossword puzzles is a condition of good learning and teaching processes, which can influence the condition of class and student including the spirit of student in following the learning process, good attention to the learning materials, courage to ask, mutual cooperation and compact in completing the task group, so that the learning process will be more active and fun, and the use of Guide Teaching method with crossword puzzles is effective in improving students' ability to correctly compile hijaiyah letter in a word with the result of t counting more larger than t table, that is 2.567> 7.60 .